2022
DOI: 10.1093/nar/gkac737
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor couples promoter recruitment of RNA processing factors to regulation of alternative polyadenylation at the 3' end of transcripts

Abstract: Prostate cancer (PC) relies on androgen receptor (AR) signaling. While hormonal therapy (HT) is efficacious, most patients evolve to an incurable castration-resistant stage (CRPC). To date, most proposed mechanisms of acquired resistance to HT have focused on AR transcriptional activity. Herein, we uncover a new role for the AR in alternative cleavage and polyadenylation (APA). Inhibition of the AR by Enzalutamide globally regulates APA in PC cells, with specific enrichment in genes related to transcription an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…6 C), which is known to dysregulate RNA processing regulation in PC [ 24 ]. Notably, several studies have recently shown that widespread alteration of 3’-end RNA processing in PC cells contributes to tumour progression [ 48 51 ]. Moreover, androgen deprivation therapy in PC cells induced a general reprogramming of APA, by promoting the pattern observed in CRPC cells [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…6 C), which is known to dysregulate RNA processing regulation in PC [ 24 ]. Notably, several studies have recently shown that widespread alteration of 3’-end RNA processing in PC cells contributes to tumour progression [ 48 51 ]. Moreover, androgen deprivation therapy in PC cells induced a general reprogramming of APA, by promoting the pattern observed in CRPC cells [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, several studies have recently shown that widespread alteration of 3’-end RNA processing in PC cells contributes to tumour progression [ 48 51 ]. Moreover, androgen deprivation therapy in PC cells induced a general reprogramming of APA, by promoting the pattern observed in CRPC cells [ 48 ]. These observations suggest that APA dysregulation contributes to PC progression and to acquisition of a therapy-resistant phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations